Psychosis, trauma, and dissociation evolving perspectives on severe psychopathology - Moskowitz, Andrew; Dorahy, Martin J. 1971; Schäfer, Ingo 1971- (John Wiley & Son Ltd., 2019)
Still the only book to focus exclusively on the relationship between dissociation and psychosis * Updated to reflect the research in this area over the past 3years * Features new chapters on hypnotisability and memory disturbances * Explains the relationship of dissociative experiences and psychotic symptoms